The impact of session-introducing mindfulness and relaxation interventions in individual psychotherapy for children and adolescents: a randomized controlled trial (MARS-CA) - Kalmar, Julia; Baumann, Ines; Schleiting, Elena; Vonderlin, Eva; Bents, Hinrich; Neubauer, Andreas B.; Heidenreich, Thomas; Mander, Johannes (Trials, 2022)
The investigation of mindfulness-based interventions (MBIs) in cognitive-behavioral therapy has greatly increased over the past years. However, most MBI research with youth focuses on structured, manualized group programs, conducted in school settings. Knowledge about the implementation and effects of MBIs in individual psychotherapy with children and adolescents is scarce. To fill this research gap, the “Mindfulness and Relaxation Study - Children and Adolescents” (MARS-CA) is designed. It aims to assess the effects of short session-introducing interventions with mindfulness elements on juvenile patients’ symptomatic outcome and therapeutic alliance in individual child and adolescent psychotherapy.